Penerapan Metode Collaborative Learning untuk Meningkatkan Pemahaman Siswa pada Materi Al Quran Hadits Siswa Kelas X IPS 2 MA Al Mahrusiyyah - Nala Rosida; Moh. Turmudi (eL Bidayah: Journal of Islamic Elementary Education, 2019)
General assumptions about the problem of education will never be discussed. Therefore, education must always be continuous in following the development of the curriculum in order to be able to anticipate all the problems that will be faced in the present and future. Education will not achieve success if one component does not participate in it. Understanding for students is needed especially in understanding learning materials to help achieve education. Understanding is the matter of authority over something that has not been understood so that it can be understood and practiced. So that student achievement increases and educational success will be achieved. This paper aims to find out learning by using Collaborative Learning methods to improve students' understanding so that student achievement increases. The method used in this study is classroom action research, which is the technique of collecting data with tests, observation and documentation. Research findings: (1) Increasing student understanding using the Collaborative Learning method. (2) High student understanding can improve student learning achievement.